Círculos de cultura em formação de professores e professoras - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The present research has as its object of study the University Extension, delimited in the relations, challenges and achievements of teacher and academic training through an extension project entitled "Circles of Culture in Teacher Training of Planaltina – GO (CIFOPLAN)". The justification for the choice of the theme is due to personal, academic, professional and social factors. To guide the research, the problem was chosen "What are the challenges and achievements of teacher training through a University Extension project?" Thus, the general objective was to present the challenges and achievements of teacher training through a University Extension project. To achieve the general objective, the research consists of the following specific objectives: to carry out a systematic literature review in order to map and analyze productions on University Extension allied to teacher training; compose a historical retrospective on University Extension; to discuss the concepts and meanings of the epistemology of University Extension; to investigate the training of teachers through critical-emancipatory praxis and to analyze the conceptions of the participants regarding CIFOPLAN in their teacher training. The research is close to Historical-Dialectical Materialism, considering the categories of totality, contradiction, mediation, omnilaterality, praxis,ontological and teleological work as an educational principle. It was configured by an applied, qualitative, exploratory-analytical, theoretical and empirical research. Theoretical, being bibliographic based on the authors Kochhann (2021a, 2021b, 2022), Sousa (2010), Síveres (2013), Reis (1996), Gurgel (1986), Curado Silva (2008, 2018a, 2018b), Saviani (2000, 2007,2011), Freire (1983a, 1983b, 1987 and 1996); Marx (1996, 2002), Thiollent (2011, 2022), among others. A Systematic Literature Review was carried out, based on Costa and Zoltowski (2014), in consultation with the database, catalogs and journals of safe websites of scientific production, delimited between the years 2018 and 2022. The empirical was an action research, based on the CIFOPLAN extension project, which was created to meet the demand requested by the Municipal Department of Education of the city of Planaltina – GO. CIFOPLAN excelled in following the methodological proposal inspired by Freire (1983a, 1987), with practices of dialogue in the sense of humanization. Thus, CIFOPLAN was held throughout 2023, consisting of 12 culture circles. The actions of CIFOPLAN were planned based on an analysis of the objective conditions carried out by the application of a mixed questionnaire. The research population comprises 176 teachers from the final groups of Elementary School, 40 undergraduates from UEG, 25 master's students from the University Unit of UEG in Luziânia. The sample was 13% of professors, 37.5% of undergraduates and 52% of master's students by inclusion and exclusion criteria for participation in the culture circles. Data collection for the research took place at various moments of the training, from the analysis of the initial objective conditions to the analysis of the final objective conditions, by means of a mixed questionnaire and field diary, through the expressions throughout the meetings. For a better deepening of the issues of teacher training by the University Extension, 5 teachers from the network were selected for a semi-structured interview, in addition to 3 undergraduates and 3 master's students. For data analysis, the Signification Center of Aguiar and Ozella (2013) was used.
Culture circles in teacher training: producing knowledge through processual, organic and critical-emancipatory praxis extension
Keywords: Formação de professores; Extensão universitária; Círculos de cultura; Teacher training; University extension.; Culture Circles; CIFOPLAN; Práxis crítico-emancipadora; CIENCIAS HUMANAS::EDUCACAO